Suppression of the pathogenicity of Candida albicans by the quorum-sensing molecules farnesol and tryptophol - Pumeesat, Potjaman; Muangkaew, Watcharamat; Wongsuk, Thanwa; Suwanmanee, San; Singkum, Pantira; Luplertlop, Natthanej (Journal of general and applied microbiology, 2019)
This study examines the ability of the quorum-sensing molecules (QSMs) farnesol and tryptophol to induce programmed cell death of the pathogenic fungus Candida albicans, to alter the expression of apoptosis-related genes, and to reduce the pathogenicity and virulence of C. albicans in Galleria mellonella. Our results showed that both farnesol and tryptophol inhibited C. albicans germ tube formation. In the QSM-treated group, the expression levels of the apoptosis genes increased, whereas the expression level of the anti-apoptosis gene decreased. Further, pretreatment of C. albicans with tryptophol or farnesol prior to G. mellonella larval infection significantly enhanced host survival compared with larvae infected with untreated C. albicans. Thus, farnesol and tryptophol may trigger apoptosis of C. albicans in vitro and reduce the virulence of C. albicans in vivo. Although further study is needed to identify the precise mechanisms underlying the antifungal properties of farnesol and tryptophol, these results suggest that QSMs may be effective agents for controlling fungal infection.